Notes on the identity and typification of Zehneria thwaitesii (Schweinf.) C.Jeffrey and Zehneria tridactyla (Hook.f.) R. Fern. & A. Fern. (Cucurbitaceae) - Bräuchler, C.; Dwivedi, Mayank D.; Schaefer, H. (Phytotaxa, 2016)
In Zehneria thwaitesii long standing uncertainties persisted with respect to taxonomic delimitation. This study is a first step in clarifying the case using both morphological and molecular phylogenetic analyses. We here provide a complete overview on the nomenclatural history of Z. thwaitesii. For the African plants hitherto included in the broadly circumscribed species the name Z. tridactyla is reinstated and a lectotype is designated. Diagnostic features distinguishing both taxa are summarised. Z. thwaitesii is now considered restricted to Asia.